The definitive guide to Squarespace : learn to deliver custom, professional web experiences for yourself and your clients - Martin, Sarah (Web developer) (Apress, 2017)
Utilize the power of Squarespace to create custom professional websites. Learn the principles and tools used by Squarespace's most successful web professionals to take your skills to the next level. Beginning with an overview of the Squarespace interface and template selection guidelines, this book shows you how the key web languages work together within Squarespace. You'll also see how to use the Custom CSS Editor, Code Injections, and Code Blocks to customize Squarespace templates and how the Style Editor selections affect the template's structure. Learn the accommodations that must be made in JavaScript for the customizations to work correctly in AJAX-based templates. Finally, discover what Developer Mode is, how to use it, and when to use it. The Definitive Guide to Squarespace is the only book you need to get up and running with Squarespace web development.